Polyvinylidene fluoride (PVDF) Nanofiber Modified Current Collector in Anode-Free Lithium Battery - Hendri Widiyandari; Adama DinaPanuntun; Hanaiyah Parasdila; Iqbal Firdaus; Agus Purwanto (Department of Physics, Sebelas Maret University, 2024)
In order to coat the layer of the Cu for an anode-free lithium battery (AFLB) and examine AFLB performance, PVDF nanofiber with electrospinning is used. The fabrication time and molecular weight of the nanofiber can be modified. In comparison to conventional models, the AFLB is one of the new model options that provides great energy density at the same battery size. The disadvantages of this new model battery include its limited electrochemical performance and the fact that it is still in its initial stages of manufacturing. Low Coulombic efficiency and uncontrolled dendritic growth are challenges in the growth of AFLB. For the fabrication of nanofiber membranes were synthesized with different types of PVDF Mw 1.300.000 and 534.000, PVDF Nanofibers were made using electrospinning with time variations of 5 hours, 7 hours, and 9 hours, and their thermal, mechanical, and porosity properties were examined. The PVDF Mw 1.300.000 sample had the greatest porosity percentage value which is 47.031% during a 9-hour time. The PVDF Mw 534.000 sample had the highest tensile strength results, with a variation of 2.33 MPa during a 9-hour time. The PVDF Mw 1.300.000 sample had the highest percentage elongation results, 39.7%. The average nanofiber size varies with processing time, with the PVDF Mw 1.300.000 sample having the smallest size at 167.9 nm.